Risk Based Accounting in Realizing Reliable Financial Governance - Tharienna Dhesta Kusuma Dewi; Farkhatun Zaidah; Al Putri Oktavia (PT. Anagata Sembagi Education, 2026)
Reliable financial governance is a fundamental prerequisite for organizational accountability and sustainability. However, conventional accounting practices that emphasize historical reporting and formal compliance have shown limitations in addressing the growing complexity of financial, operational, and compliance risks in modern governance. This study aims to analyze the concept of Risk Based Accounting and its role in realizing reliable financial governance. The study employs a qualitative normative–conceptual approach through a literature review of accounting standards, financial governance principles, risk management frameworks, and reputable academic sources. The analysis examines the conceptual relationship between risk, accounting practices, and reliable financial governance. The findings indicate that Risk Based Accounting reorients accounting from retrospective, compliance-based reporting toward a preventive and forward-looking risk-based approach. Integrating risk into accounting practices enhances the quality of financial information, strengthens substantive transparency, and supports more accountable financial decision-making and oversight. This study concludes that Risk Based Accounting constitutes a strategic instrument for strengthening reliable financial governance, provided that it is supported by a clear conceptual framework and consistent normative harmonization.